Can we have a second light Higgs boson in the \(U(1)\) model? - Do, Thi Huong; Nguyen Tuan, Duy (Communications in Physics, 2025)
Our theoretical model predicts the existence of a light-mass CP-even Higgs boson (\(\mathcal{H}_1\)) and a light-mass pseudo-scalar boson (\(\mathcal{A}\)). The mass ranges for these particles are determined by the cubic coupling, \(μ_4\), at the electroweak energy scale. These light Higgs bosons can produce flavor-changing neutral currents, which play a significant role in meson mixing processes. Specifically, when \(m_\mathcal{A} = s_α m_{\mathcal{H}_1}\), the contributions to flavor mixing can either completely cancel each other out or, conversely, become extremely large.